2017
DOI: 10.1038/srep44710
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal conductivity of form-stable phase change composite with single-walled carbon nanotubes for thermal energy storage

Abstract: A striking contrast in the thermal conductivities of polyethylene glycol (PEG)/diatomite form-stable phase change composite (fs-PCC) with single-walled carbon nanotubes (SWCNs) as nano-additive has been reported in our present study. Compared to the pure PEG, the thermal conductivity of the prepared fs-PCC has increased from 0.24 W/mK to 0.87 W/Mk with a small SWCNs loading of 2 wt%. SWCNs are decorated on the inner surface of diatomite pores whilst retaining its porous structure. Compared to PEG/diatomite fs-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 17 publications
6
21
0
4
Order By: Relevance
“…Figures 6 a,b show the thermal degradation of CDs and CDs-PEG synthesized by hydrothermal carbonization at the same condition at 220 °C for 6 h. It was observed that CDs-220C-6h showed the slow decomposition according to the heating time, however CDs-PEG showed the rapid degradation at temperature 400 °C regarding the breakdown of PEG molecules passivated on CDs. From the previous report, PEG (Mw = 6000) was thermally decomposed starting from 250 to 400 °C for complete decomposition of PEG 50 . With narrow DTG peak from CDs-PEG illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Figures 6 a,b show the thermal degradation of CDs and CDs-PEG synthesized by hydrothermal carbonization at the same condition at 220 °C for 6 h. It was observed that CDs-220C-6h showed the slow decomposition according to the heating time, however CDs-PEG showed the rapid degradation at temperature 400 °C regarding the breakdown of PEG molecules passivated on CDs. From the previous report, PEG (Mw = 6000) was thermally decomposed starting from 250 to 400 °C for complete decomposition of PEG 50 . With narrow DTG peak from CDs-PEG illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 6, the increment ratios in thermal conductivities of the composite PCMs with CNT doping were compared to different clay-based composite PCMs doped with carbon-based additives. 37,6773 As obviously seen, especially in case of 5 wt% CNTs adding, the increase percentage in thermal conductivity was higher than that of most of the CPCMs. This evaluation exhibits that the improvement in thermal conductivity of the CPCMs can be changed considerably depending on the thermal conductivity of main supporting matrix, additive material and their mass fractions.…”
Section: Resultsmentioning
confidence: 81%
“…This can be explained by two cases: First, since the CA is held in the porous structure of both carbon materials by the capillary and surface tension forces, its movement which causes the delay of its crystallization is restricted, thereby become more quickly solidified 40 . The second case might be that the supporting CHW and ACHW materials provide heat conduction paths, thereby accelerating the phase transition speed of the CA 20 …”
Section: Resultsmentioning
confidence: 99%
“…During the melting and solidification phase transformations, PCMs perform LHTES function, while the supporter materials prevents PCM seepage in liquid state and ensures the solid shape to be fully preserved 12‐16 . Some of the porous materials commonly used in the production of shape stable composites are attapulgite, 17 expanded perlite, 18 sepiolite, 11 vermiculite, 19 diatomite 14,20 and silica fume 8,21 . However, many of these materials themselves have low thermal conductivity and hence it is obvious that they cannot help increase the thermal conductivity of PCMs.…”
Section: Introductionmentioning
confidence: 99%